2007
DOI: 10.1002/chin.200748140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X‐Ray Structure, and Pharmacological Activity of Some 6,6‐Disubstituted Chromeno[4,3‐b]‐ and Chromeno[3,4‐c]‐quinolines.

Abstract: Fused pyridine derivatives R 0450Synthesis, X-Ray Structure, and Pharmacological Activity of Some 6,6-Disubstituted Chromeno[4,3-b]-and Chromeno[3,4-c]-quinolines. -A variety of new chromeno[4,3-b]quinolines (V) is synthesized by reaction of chromenecarboxaldehydes (III) with anilines. Surprisingly, (III) react with 2-aminothiophenol to furnish chromeno[3,4-c]quinolines (VII) via extrusion of sulfur from intermediate thiazepines. Compounds (Vb) and (VIIb) show significant antiinflammatory and ulcerogenic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The results obtained from the spectra were consistent with the assigned structures of the compounds. The 1 HNMR and 13 CNMR spectra as well as the reaction schemes for the synthesis of the above compounds are outline in the Figs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) The synthesized compounds were subjected to molecular docking with a target protein, 1CVU to compare their binding energies with celecoxib and rofecoxib which are used as standard drugs for the inhibition of COX2 enzyme, Kurumbail (1994). From the docking result, the binding energy values of the above synthesized compounds were found to be -5.8 kJmol -1 , -6.2 kJmol -1 , -7.2 kJmol -1 , -7.4 kJmol -1 and -7.6 kJmol -1 respectively as shown in table 1 and the chart in Fig 23 below.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from the spectra were consistent with the assigned structures of the compounds. The 1 HNMR and 13 CNMR spectra as well as the reaction schemes for the synthesis of the above compounds are outline in the Figs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) The synthesized compounds were subjected to molecular docking with a target protein, 1CVU to compare their binding energies with celecoxib and rofecoxib which are used as standard drugs for the inhibition of COX2 enzyme, Kurumbail (1994). From the docking result, the binding energy values of the above synthesized compounds were found to be -5.8 kJmol -1 , -6.2 kJmol -1 , -7.2 kJmol -1 , -7.4 kJmol -1 and -7.6 kJmol -1 respectively as shown in table 1 and the chart in Fig 23 below.…”
Section: Resultsmentioning
confidence: 99%
“…2,3-Dihydro-2,2-dimethylchromen-4-one (1a) (12), 2,3-dihydro spirochromen(2,1') cyclohexane-4-one (1b) (13), 2,3-dihydro-2-ethyl-2-methylchromen-4-one (1c) (12), 4--chloro-2,2-dimethyl-2H-chromene (2a) (14), 4-chloro spiro-2H-chromene(2,1')cyclohexane (2b) (15), 4-chloro-2-ehyl-2-methyl-2H-chromene (2c) (16), 4-chloro-2,2-dimethyl-2H--chromene-3-carbaldehyde (3a) (6), 4-chloro spiro-2H-chromene(2,1')cyclohexane-3-carbaldehyde (3b) (6), and 4-chloro-2-ethyl-2-methyl-2H-chromene-3-carbaldehyde (3c) (16) were prepared according to the literature.…”
Section: Methodsmentioning
confidence: 99%
“…A combination of benzopyran or chromen with a quinoline moiety in a single molecule, for example, 6H-chromeno[4,3-b]quinoline (Vu et al, 2007;Hegab et al, 2007 ) or 1-benzopyrano[3,4 -f]quinoline (Tabakovic et al, 1983) have also been identified for the promising bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%